Household Smoking Behaviour: Insights from the 2024 Clean and Healthy Living Behaviour (PHBS) Survey, Puskesmas Lempake - Andi Rahmad Jaya; Nur Rohmah; Annisa Nurrachmawati (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Based on the 2024 Clean and Healthy Living Behaviour (PHBS) Household Survey conducted in the working area of UPTD Puskesmas Lempake, the indicator of “not smoking inside the home” showed an achievement rate of 77.6%, which remains below the national target of 85%. This finding indicates that many household members are still not fully aware of the health risks associated with exposure to cigarette smoke, particularly for children and pregnant women [2]. Smoking indoors increases the risk of respiratory illnesses and other non-communicable diseases, such as asthma, heart disease, and lung cancer. Objective : This study aims to describe smoking behaviour among households, identify factors contributing to indoor smoking practices, and emphasize the importance of health promotion interventions to support smoke-free homes Research Methods/ Implementation Methods : This study was a descriptive study design using secondary data from 264 household heads who participated in the 2024 PHBS survey Results : The analysis revealed that while most households understood the dangers of smoking, indoor smoking still occurred, particularly during leisure activities and family gatherings. The persistence of social smoking norms and low awareness of the risks of secondhand smoke, especially for children and pregnant women, were identified as contributing factors. These findings suggest that indoor smoking remains a challenge in realizing clean and healthy living behaviours within the community. Conclusion/Lesson Learned : Strengthened health education, empowerment of community health workers, and cross-sectoral collaboration are needed to encourage behavioural change and family commitment toward smoke-free households, ultimately creating a healthier living environment.